Transoral Robotic Surgery in the Management of a Tongue Base Schwannoma. Issue 4 (June 2020) - Petruzzi, Gerardo; Costantino, Andrea; Arosio, Alberto Daniele; De Virgilio, Armando; Pichi, Barbara; Zocchi, Jacopo; Mercante, Giuseppe; Spriano, Giuseppe; Pellini, Raul
Abstract : Abstract: Schwannomas are the most common benign tumors arising from the peripheral nerve sheath, and the intraoral location is very atypical, representing less than 1% of all cases. Surgical excision is the treatment of choice, and a variety of surgical approaches have been described. The authors report the first described case of tongue base schwannoma treated with transoral robotic surgery (TORS). A 47-years-old female patient complaining mild dysphagia and snoring, presented a submucosal swelling at the right side of the tongue base. MRI showed a large well-circumscribed solid mass, homogeneously isointense in T1WI and hyperintense on T2WI, with no lymph node metastasis. According to size, location and radiological characteristic of the mass a TORS approach was chosen. An extracapsular dissection was performed, and the lesion was completely removed with no intraoperative complications. The final diagnosis based on histopathological examination and IHC analysis (S-100 positive) was a schwannoma of the tongue base. The post-operative course was uneventful, and no recurrence was observed after 6 months of follow-up. This study demonstrates the feasibility of TORS in the treatment of a tongue base schwannoma. This is a valid alternative to the common transoral approach in order to avoid more invasive external approaches, and further studies are recommended in order to clarify if this approach could be proposed as the first line treatment in selected cases.